Development of the symptoms and impacts questionnaire for Crohn's disease and ulcerative colitis. Issue 11 (21st April 2020) - Dulai, Parambir S.; Jairath, Vipul; Khanna, Reena; Ma, Christopher; McCarrier, Kelly P.; Martin, Mona L.; Parker, Claire E.; Morris, Joan; Feagan, Brian G.; Sandborn, William J.
Summary: Background: Patient‐reported outcome (PRO) measures historically used in inflammatory bowel disease have been considered inadequate to support future drug labelling claims by regulatory agencies. Aims: To develop PRO tools for use in Crohn's disease (CD) and ulcerative colitis (UC) following guidance issued by the US FDA and the ISPOR (International Society for Pharmacoeconomics and Outcomes Research). Methods: Concept elicitation and cognitive interviews were conducted in adult patients (≥18 years) across the United States and Canada. Semi‐structured interview guides were used to collect data, and interview transcripts were coded and analysed. Concept elicitation results were considered alongside existing literature and clinical expert opinion to identify candidate PRO items. Cognitive interviews evaluated concept relevance, interpretability and structure, and facilitated instrument refinement. Concept elicitation participants, except those with an ostomy, underwent centrally read endoscopy to assess inflammatory status. Results: In all, 54 participants (mean age: 46.2 years; 66.7% female) were included in the CD concept elicitation interviews. In total, 80 symptom concepts and 61 impact concepts were identified. After three waves of cognitive interviews, the 31‐item Symptoms and Impacts Questionnaire for CD (SIQ‐CD) was developed. In the UC concept elicitation phase, 53 participants were interviewed (mean age: 41.4 years; 49.1% female). In total, 79 symptoms concepts and 49 impact concepts were identified. Following two waves of cognitive interviews, the 29‐item Symptoms and Impacts Questionnaire for UC (SIQ‐UC) was developed. Both instruments include four symptom and six impact domains. Conclusions: We developed PROs to support CD and UC drug labelling claims. Psychometric validation studies to evaluate instrument reliability and responsiveness are ongoing.